2024
DOI: 10.1007/s15010-023-02163-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and antimicrobial resistance of invasive Escherichia coli disease in hospitalized older adults: a prospective multinational observational study

Joachim Doua,
Jesús Rodríguez-Baño,
Rachel Froget
et al.

Abstract: Background Clinical data characterizing invasive Escherichia coli disease (IED) are limited. We assessed the clinical presentation of IED and antimicrobial resistance (AMR) patterns of causative E. coli isolates in older adults. Methods EXPECT-2 (NCT04117113) was a prospective, observational, multinational, hospital-based study conducted in patients with IED aged ≥ 60 years. IED was determined by the microbiological confirmation of E. coli from blood; or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Our study revealed that urinary tract infections were the most common infectious site among elderly sepsis patients (38%), followed by pulmonary (30%), abdominal (20%), and other sites (18%). This nding aligns with prior research conducted by J. Doua et al 21 , which also identi ed the urinary tract as the primary source of infection (62.9%), followed by intraabdominal infection (20.4%), other (14.2%), and respiratory tract (2.5%).…”
Section: Discussionsupporting
confidence: 90%
“…Our study revealed that urinary tract infections were the most common infectious site among elderly sepsis patients (38%), followed by pulmonary (30%), abdominal (20%), and other sites (18%). This nding aligns with prior research conducted by J. Doua et al 21 , which also identi ed the urinary tract as the primary source of infection (62.9%), followed by intraabdominal infection (20.4%), other (14.2%), and respiratory tract (2.5%).…”
Section: Discussionsupporting
confidence: 90%